An adaptive controller of hydro generators for smart grid application in Malaysia - Mohamad, H.; Bakar, A.H.A.; Ping, H.W.; Mokhlis, Hazlie (IEEE, 2010)
An intentional islanding operation or a planned islanding operation is feasible with the advance technologies introduced by a smart distribution system. This paper highlights a well planned islanding operation facilitating with an intelligent control strategy for a Distributed Generation (DG) to operate islanded and cater the issue of different islanding area. For radial system network, the DG could be serving several islanding areas as a result of different fault locations. For each islanding area, the governor's controller is properly designed such that the DG exhibits a good dynamic response once a part of the network is islanded. A means to automatic synchronized the islanded network with the grid for reconnection process is also considered in the controller. The controller has been modeled considering the existing Malaysia' distribution network of mini hydro power plant connected in parallel to the grid. The transient stability response of the generator is observed particularly on the frequency not to exceed the maximum allowable protection setting. The results proved that the DGs are feasible to operate in the islanded system despites slow dynamic response of hydro turbine to reach steady state. In addition, the slow transient response of hydro governor turbine has given a challenge in designing the controller algorithm.